2005
DOI: 10.4088/jcp.v66n1109
|View full text |Cite
|
Sign up to set email alerts
|

The Selective GABA Reuptake Inhibitor Tiagabine for the Treatment of Generalized Anxiety Disorder

Abstract: To evaluate the efficacy and tolerability of tiagabine, a selective γ-aminobutyric acid (GABA) reuptake inhibitor, in adults with generalized anxiety disorder (GAD). Method: This 8-week, randomized, doubleblind, multicenter, placebo-controlled study enrolled patients with GAD (DSM-IV). Tiagabine was initiated at 4 mg/day and then flexibly dosed twice a day to a maximum dose of 16 mg/day. Study drug was tapered after week 8 in decrements of 2 mg every other day. Efficacy assessments included the Hamilton Rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 25 publications
3
38
1
1
Order By: Relevance
“…Other studies suggest marked impairment relative to other anxiety disorders, but at levels that may be less than major depression [2]. Randomized clinical trials comparing the efficacy of different treatment modalities of PD have demonstrated that, in addition to symptomatic improvement, treated patients with PD report significant improvements in their QoL [5,6,7,8,9]. However, few studies have assessed individual dimensions of QoL (e.g., physical, social, general functioning, mental health and general health perception) [2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest marked impairment relative to other anxiety disorders, but at levels that may be less than major depression [2]. Randomized clinical trials comparing the efficacy of different treatment modalities of PD have demonstrated that, in addition to symptomatic improvement, treated patients with PD report significant improvements in their QoL [5,6,7,8,9]. However, few studies have assessed individual dimensions of QoL (e.g., physical, social, general functioning, mental health and general health perception) [2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…3 However, we should mention the possible temporal delay of TGB -one week -to bring about its anxiolytic effects. 4 Although anecdotic and thus warranting replication in large and wellcontrolled studies, the findings of our case report suggest that TGB might be a promising new pharmacological agent in the treatment of BDZ dependence. OR 10 CONSECUTIVE years the suicide rate in Japan has stayed at around 25 per 100 000, which is the highest among the developed countries.…”
mentioning
confidence: 65%
“…Παρ' όλα αυτά, σύμφωνα με την έρευνα του Noyes και των συνεργατών του (1987), αλλά και με τον Torgesen (1986), ο περιβαλλοντικός παράγοντας συνδέεται με την εμφάνιση της διαταραχής (Βασιλάκη, 2008). Επίσης, σύμφωνα με το Harvard-Brown Anxiety Research Program, οι λιγότεροι από τους μισούς ασθενείς με ΓΑΔ αντιμετώπισαν μερικώς ή οριστικά τη διαταραχή και το 27% απ' αυτούς εμφάνισε και πάλι τη διαταραχή (Pollack, Roy-Byrne, Ameringen, Snyder, Brown, Ondrasik & Rickels, 2005).…”
Section: γενικευμένη αγχώδης διαταραχήunclassified